SISTEM INFORMASI PENYEWAAN DAN PEMESANAN TIKET BUS DAN TRAVEL KOTA PADANG - Hanif Efriko Pratama; Elfi Tasrif; Ahmadul Hadi (Universitas Negeri Padang, 2017)
Padang City, as one of populous city in West sumatera province, well known as their wandering culture. This wandering culture causes the number of people using public transport to go out increased, especially the Inter-City Inter-Provincial bus (AKAP) users. Unfortunately, high public interest in using AKAP buses has not been supported by the adequate system of AKAP bus companies. Current system affect prospective passengers into problems while searching for the location of a transport company. It caused by limited source of information media, such as banners or word-of-mouth information. This lack of information reducing the user's comfort in using AKAP bus. This Information system of rental and booking bus and travel tickets in Padang City was created using the PHP programming language using the CodeIgniter framework and MYSQL for the database. The design of this information system is done to produce a web-based information system that provides information of transportation companies location to facilitate passengers and prospective passengers to come, and facilitate the process of booking tickets. The design of this information system displays the location information, prices, facilities, and transportation fleet that available in each company. Keywords: Information system, AKAP bus, transportation.